2017
DOI: 10.3389/fcimb.2017.00344
|View full text |Cite
|
Sign up to set email alerts
|

Alloiococcus otitidis Forms Multispecies Biofilm with Haemophilus influenzae: Effects on Antibiotic Susceptibility and Growth in Adverse Conditions

Abstract: Otitis media with effusion (OME) is a biofilm driven disease and commonly accepted otopathogens, such as Haemophilus influenzae, Streptococcus pneumonia, and Moraxella catarrhalis, have been demonstrated to form polymicrobial biofilms within the middle ear cleft. However, Alloiococcus otitidis (A. otitidis), which is one of the most commonly found bacteria within middle ear aspirates of children with OME, has not been described to form biofilms. The aim of this study was to investigate whether A. otitidis can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
(59 reference statements)
1
15
0
1
Order By: Relevance
“…A. otitidis has been frequently documented as one of the most prevalent bacteria in middle ear aspirates of patients with otitis media with effusion [25]. Recently, it was reported that A. otitidis plays a role in the pathogenesis of otitis media with effusion, in which it forms both single- and multi-species biofilms with other bacteria, thus promoting multidrug resistance [26].…”
Section: Resultsmentioning
confidence: 99%
“…A. otitidis has been frequently documented as one of the most prevalent bacteria in middle ear aspirates of patients with otitis media with effusion [25]. Recently, it was reported that A. otitidis plays a role in the pathogenesis of otitis media with effusion, in which it forms both single- and multi-species biofilms with other bacteria, thus promoting multidrug resistance [26].…”
Section: Resultsmentioning
confidence: 99%
“…The number of viable cells of S. suis in the presence of norfloxacin was tested using the protocol described (Chan et al, 2017). In brief, the 96-well microtiter plate were filled with S. suis(1/100 dilution) and added the presence of norfloxacin.…”
Section: Colony Forming Unit Assaymentioning
confidence: 99%
“…In addition, A. otitidis is able to form both single- and multispecies biofilms with Haemophilus influenzae . When present in polymicrobial biofilms, A. otitidis can promote H. influenzae growth and survival by increasing biofilm production in adverse growth conditions and by altering antimicrobial resistance [ 27 ]. In this study, the use of antibiotics ≤ 6 months prior to inclusion in the study did not have an effect on the detection of Alloiococcus spp., Haemophilus spp., Streptococcus spp., or Moraxella spp.…”
Section: Resultsmentioning
confidence: 99%